Diversity, Dynamics and Therapeutic Application of Clostridioides difficile Bacteriophages - Janet Y. Nale; Anisha M. Thanki; Srwa J. Rashid; Jinyu Shan; Gurinder K. Vinner; Ahmed S. A. Dowah; Jeffrey K. J. Cheng; Thomas Sicheritz-Pontén; Martha R. J. Clokie (Viruses, 2022)
Clostridioides difficile causes antibiotic-induced diarrhoea and pseudomembranous colitis in humans and animals. Current conventional treatment relies solely on antibiotics, but C. difficile infection (CDI) cases remain persistently high with concomitant increased recurrence often due to the emergence of antibiotic-resistant strains. Antibiotics used in treatment also induce gut microbial imbalance; therefore, novel therapeutics with improved target specificity are being investigated. Bacteriophages (phages) kill bacteria with precision, hence are alternative therapeutics for the targeted eradication of the pathogen. Here, we review current progress in C. difficile phage research. We discuss tested strategies of isolating C. difficile phages directly, and via enrichment methods from various sample types and through antibiotic induction to mediate prophage release. We also summarise phenotypic phage data that reveal their morphological, genetic diversity, and various ways they impact their host physiology and pathogenicity during infection and lysogeny. Furthermore, we describe the therapeutic development of phages through efficacy testing in different in vitro, ex vivo and in vivo infection models. We also discuss genetic modification of phages to prevent horizontal gene transfer and improve lysis efficacy and formulation to enhance stability and delivery of the phages. The goal of this review is to provide a more in-depth understanding of C. difficile phages and theoretical and practical knowledge on pre-clinical, therapeutic evaluation of the safety and effectiveness of phage therapy for CDI.